2007
DOI: 10.1021/bi602415u
|View full text |Cite
|
Sign up to set email alerts
|

Double-Mutant Cycle Scanning of the Interaction of a Peptide Ligand and Its G Protein-Coupled Receptor

Abstract: The interaction between the yeast G protein coupled receptor (GPCR), Ste2p, and its α-factor tridecapeptide ligand was subjected to double-mutant cycle scanning analysis by which the pairwise interaction energy of each ligand residue with two receptor residues, N205 and Y266, was determined. The mutations N205A and Y266A were previously shown to result in deficient signaling but cause only a 2.5-fold and 6-fold decrease, respectively, in the affinity for α-factor. The analysis shows that residues at the amine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…These substitutions had previously been reported to interact with bound ligand 15; 16; 22; 25 but were not recovered from our screen. However, each of these substitutions resulted in large decreases in the FL1/FL2 ratios of bound [Lys 7 (NBD),Nle 12 ]α-factor.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These substitutions had previously been reported to interact with bound ligand 15; 16; 22; 25 but were not recovered from our screen. However, each of these substitutions resulted in large decreases in the FL1/FL2 ratios of bound [Lys 7 (NBD),Nle 12 ]α-factor.…”
Section: Resultsmentioning
confidence: 96%
“…While Ste2p exhibits little sequence similarity to mammalian GPCRs, it is functionally interchangeable with some mammalian receptors 10; 11 . Several residues in the receptor that interact with ligand have been identified by chemical crosslinking and by characterizing amino acid substitutions in the ligand and receptor 12; 13; 14; 15; 16; 17; 18 . However, given the size of α-factor, it is likely that additional residues in Ste2p interact with bound peptide.…”
Section: Introductionmentioning
confidence: 99%
“…6D) , and Leu 4 of the pheromone, suggesting that the N terminus of ␣-factor interacts cooperatively with residues at the TM5 and TM6 extracellular surface (43). Thus, binding of the tridecapeptide might disrupt and transform existing networks of interactions between various Ste2p residues to form a new network of interactions between the ␣-factor residues and Ste2p, resulting in the propagation of a conformational change across the receptor and G protein signaling.…”
Section: Discussionmentioning
confidence: 99%
“…9). Double mutant-cycle analyis (42) previously showed that Trp 1 and Trp 3 of α-factor interact strongly with N205 and Y266 residues that are located near the extracellular ends of TM5 and TM6, respectively (17, 52). Finally, the center of α-factor is thought to face toward the extracellular loop regions of Ste2p (17, 33).…”
Section: Discussionmentioning
confidence: 99%